TEKS HUMOR DALAM WATTPAD SEBAGAI BAHAN AJAR PEMBELAJARAN BAHASA INDONESIA - Ani Rufiah; Agus Budi Wahyudi (Kajian Linguistik dan Sastra, 2022)
Humor provides a positive side in the form of a more pleasant atmosphere and causes laughter This study aims to (1) describe humorous texts in Wattpad (2) use humorous texts as teaching materials for Indonesian language learning. The data used in this research is humor text in Wattpad. While the data sources used in this study are 8 (eight) Wattpads containing humorous texts. The data collection used in this research is the method of observing and recording. The data analysis technique related to this research uses the pragmatic equivalent and referential equivalent method with the determining element sorting technique. The validity of the data in the study used theoretical triangulation. The results of this study (1) types of humorous texts include social humor, romantic humor, family humor, and educational humor, and (2) Humor texts in Wattpad are used as teaching materials in learning Indonesian in SMA class X according to the 2013 Curriculum. That is, humor can liven up an exciting atmosphere, make it a means of entertainment, not tense and can help build good feelings between students and teachers.